1998
DOI: 10.1203/00006450-199810000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Development of Human Newborn Cerebral White Matter Assessed in Vivo by Diffusion Tensor Magnetic Resonance Imaging

Abstract: Alterations of the architecture of cerebral white matter in the developing human brain can affect cortical development and result in functional disabilities. A line scan diffusion-weighted magnetic resonance imaging (MRI) sequence with diffusion tensor analysis was applied to measure the apparent diffusion coefficient, to calculate relative anisotropy, and to delineate three-dimensional fiber architecture in cerebral white matter in preterm (n = 17) and full-term infants (n = 7). To assess effects of prematuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

40
518
4
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 652 publications
(565 citation statements)
references
References 23 publications
40
518
4
3
Order By: Relevance
“…Two or more brains have been investigated at all gestational ages, and in all cases the inter-animal variability is less than inter-age-group variability (data not shown). The diminishing gray-white contrast of D av maps with increasing gestational age is identical to the observations for the human infant (Huppi et al, 1998;Neil et al, 1998). Furthermore, the principal axis of diffusion in cerebral cortex is oriented radially, as has been shown for developing human cortex (McKinstry et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Two or more brains have been investigated at all gestational ages, and in all cases the inter-animal variability is less than inter-age-group variability (data not shown). The diminishing gray-white contrast of D av maps with increasing gestational age is identical to the observations for the human infant (Huppi et al, 1998;Neil et al, 1998). Furthermore, the principal axis of diffusion in cerebral cortex is oriented radially, as has been shown for developing human cortex (McKinstry et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…Diffusion MRI, in particular, is being applied to assess brain development (Huppi et al, 1998;Neil et al, 2002;Partridge et al, 2004;Rutherford et al, 2004). Diffusion MRI provides information about the directional dependence of water displacements due to diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies of similar cohorts, we and others have observed decreased frontotemporal volume, increased thalamic diffusivity, and decreased FA in the central white matter with increasing prematurity 7, 10, 12, 35. Here, we show these changes are coupled, independent of age at scan and total intracranial volume, and exacerbated by comorbid markers of neonatal sickness.…”
Section: Discussionsupporting
confidence: 78%